Prison Management in light of Technological Developments - Othman Ali Mohammed Al-Tuhami; Ezzedine Mohammed Ali (International Journal of Law Research and Studies, 2025)
This research is characterized by development and progress. It examines the importance of integrating technology into prison management and its ability to enhance security, improve work performance, and enhance the environment. It also examines its effective impact on prisoners, enabling them to be rehabilitated through education, vocational training, and psychological support. It also examines the challenges facing technology in prisons, such as cybercrime, which has become a common crime in recent times. It attempts to develop appropriate solutions through cybersecurity agencies and the maintenance of the digital infrastructure of prison institutions.